P38 Integrative literature-review on shared decision-making, advance care planning, including values and preferences of elderly patients with symptomatic aortic valve stenosis. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Rogger, NM; Drewniak, D; Krones, T
Abstract : Background: Only very few studies have been published on Shared Decision-Making (SDM) and Advance Care Planning (ACP) including high risk patients with aortic valve stenosis addressing transcatheter aortic valve replacement (TAVR), surgical valve replacement (SAVR) and palliative care as treatment options. Therefore, the aim of this study is to strengthen the basis for further investigations on this increasingly important theme. Methods: We currently perform a computerized integrated literature review of MedLine (PubMed), EMBASE and Cochrane databases, including among others the MeSH terms aged, frail, aortic valve stenosis, advance care planning, and sensitive search filters on health outcomes such as patient values and health care related quality of life. Qualitative and quantitative studies are both included. For quality evaluation we will use the method of systematic review developed by Hawker et al. (2002) and based on the Critical Appraisal Program (CASP) tool for qualitative research. Since a great variability of the study types can be expected, they will be systemized using thematic analysis approach. Results: We will present the ethical and practical relevance of this specific topic with regard to Advance Care Planning and Shared Decision-Making and present first results of our integrated literature review.